Teaching Styles and Motivational Practices of Grade 6 Mathematics Teachers in Tinglayan District, Kalinga - Chac-Ip, Sheryl; Sabado, Adriano (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the perceptions of Grade 6 Mathematics teachers in Tinglayan District, Kalinga, regarding their motivational practices, teaching styles, and problems encountered in Mathematics instruction. A descriptive-survey design was used, involving twenty Grade 6 Mathematics teachers during School Year 2025-2026. Data were gathered through a structured questionnaire, informal interviews, and documentary analysis, and were treated using frequency count, percentage, and weighted mean. Findings showed that the teachers were mostly female, married, Teacher III, holders of a master’s degree in education, and recipients of outstanding performance ratings. The teachers agreed that they used motivational strategies in teaching Grade 6 Mathematics, with presenting a challenge receiving the highest rating, followed by indicating the usefulness of a topic and using recreational Mathematics. In terms of teaching styles, teaching by example received the highest rating, followed by providing feedback and establishing learning goals, expectations, and rules of conduct. Problems encountered in Mathematics teaching were slightly serious, with limited community participation in Mathematics activities rated as the most serious concern. The study concludes that Grade 6 Mathematics teachers in Tinglayan District use varied motivational strategies and teaching styles that support pupils’ engagement in Mathematics learning. Stronger community participation, sustained professional development, and adequate instructional resources remain necessary to strengthen Mathematics instruction.